Bifunctional Ligand Enables Efficient Gold‐Catalyzed Hydroalkenylation of Propargylic Alcohol. (4th June 2018) - Liao, Shengrong; Porta, Alessio; Cheng, Xinpeng; Ma, Xu; Zanoni, Giuseppe; Zhang, Liming
Abstract: Using the previously designed biphenyl‐2‐ylphosphine ligand, featuring a remote tertiary amino group, the first gold‐catalyzed intermolecular hydroalkenylation of alkynes has been developed. Synthetically valuable conjugated dienyl alcohols are formed in moderate to good yields. A range of alkenyltrifluoroborates are allowed as the alkenyl donor, and no erosion of alkene geometry and/or the propargylic configuration are detected. DFT calculations confirm the critical role of the remote basic group in the ligand as a general‐base catalyst for promoting this novel gold catalysis with good efficiency.